Media Video Company Profile Penunjang Informasi Dan Promosi PT. Harafiel Trijaya - Sendy Zul Friandi; Hendra Kusumah; Muhammad Aditya Rifky Cahyadi (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
The internet has become the life of every human being, the internet has several types such as text, images, photos, sound, video and audio-visual. Every company, whether large, medium, or small-scale companies need something called a company profile as well as PT. Harafiel Trijaya. Currently PT. Harafiel Trijaya still uses promotion by means of promotional designs which are deemed insufficient for its dissemination to the wider community, so it is necessary to make a very good profile video so that the public or potential customers know a lot about PT. Harafiel Trijaya. PT. Harafiel Trijaya is engaged in the construction service industry (Engineering and Construction) which includes Civil Works, Building and Architecture Works, Mechanical and Electrical Works. This video company profile was created using video support applications such as Adobe Premiere Pro.